Microbial abundance reference to t]he e.coii in the water column at casurina reef, jaffna nothern, sri lanka - Sankalpa, D.M.R.; Kuganathan, S.; Thavaranjith, A.C. (Research Gate, 2018)
Coral reefs ecosystems are sensitive to global changes in climate and human activities. The relationship between microbial activity and chemical substances available in the water column due to sensitt've process from climate to human activity is not very clear. This area ol research is needed to understand the ecosystem processes for conservation initiatives. Therefore this study aims to identify the current status of shallow coral reef casurina at Karainagar Jaffna North Sri Lanka (9.46'19.75"N,79.53,33.47,,E) from August 2015 to of April 2016' with reference to E'coli as an indicator, activity ani quatity of water in reef water' chemical conditions of sea water were measured, following parameters were used to assess viz. Dissolved Oxygen (DO), Temperature (T), Salinity (S), Deptir (D), (pH) . E.coli and Total Bacterial abundance was measured using direct counting method. Also culture experiments to show the microbes' selective agar plates (Endo Agar*fo r E.coliand, Nutrient Agar for total bacteria). Results disclosed rhat water quality (DO:9.7g + 0.31 ppm, T:2g.53 + 1'76"C, 5:34.5 +3.42ppt, D:0.56 + 0.08 m, pH=g.10 + 0.12) and microbial abundance (MA) (mean Total MA:6.grxr06 ml-r, mean E.cori abundance:3.96x106 ml-rat casurina reef were within the range of suitable condition for growth of corals and other associated organisms' Continuous monitoring is essential to describe the situations with relation to changes of climate of human activity.
Keywords: Coral; Seawater; E.coli; Water column